18‐month outcomes of a community‐based treatment for childhood obesity. Issue 3 (10th September 2013) - Foster, G. D.; Sundal, D.; Lent, M. R.; McDermott, C.; Jelalian, E.; Vojta, D.
Summary Background Few studies have evaluated community‐based interventions for childhood obesity and even fewer provide efficacy data 1 year later. Objectives This study assessed changes in relative weight 1 year after a 6‐month treatment for childhood obesity. Methods Participants were 155 overweight/obese children/adolescents and their caregivers. The primary outcome was change in child percent over body mass index (BMI) from 6 to 18 months. The primary outcome was also assessed from 0 to 18 months and changes in secondary outcomes (BMI z‐score, guardian weight, health‐related quality of life [HRQoL]) were examined from 6–18 to 0–18 months. Results From 6 to 18 months, there were no significant changes in any outcome. From 0 to 18 months, there were improvements in BMI z‐score (P < 0.001), HRQoL (P < 0.001) and guardian weight (P = 0.02). Conclusions Changes in relative weight and HRQoL observed after 6 months persisted 1 year later. The programme produced reductions in BMI z‐score and obesity prevalence but not in percent over BMI from 0 to 18 months.